WorldwIde SurvEy on Clinical and Anatomical Factors Driving the Choice of Transcatheter Aortic Valve pRostheses - Biasco, Luigi; Cerrato, Enrico; Tersalvi, Gregorio; Pedrazzini, Giovanni; Wilkins, Ben; Faletra, Francesco; Ferrari, Enrico; Demertzis, Stefanos; Senatore, Gaetano; Di Leo, Angelo; Varbella, Ferdinando; De Backer, Ole; et al. (Frontiers in Cardiovascular Medicine, 2020)
Background Following the success of the first human transcatheter aortic valve replacement (TAVR) in 2002, multiple transcatheter heart valves (THVs) have become available. However, guidelines or expert consensus on how to optimize THV choice according to patients’ anatomical and clinical characteristics is missing. This survey-based study aimed to identify patient-specific characteristics deemed important in the choice of THV type. Methods and results A web-based survey including 39 questions was completed by 71 experienced TAVR operators from 23 countries with a median TAVR volume of 88, procedures in the year prior to survey completion (IQR 61-180). The survey covered five topics: access, aortic annulus/leaflets, aortic root, left ventricular function, and clinical characteristics. Factors with the most impact on THV choice were reported to be a calcified sinotubular junction, valve-in-valve procedure, annular dimension > 575 mm2, femoral diameter ≤ 5.0 mm, low coronary ostia, calcification at the annulus level and/or protruding into the left ventricular outflow tract, and need for post TAVR PCI. Also, in case of off-label use of THVs to treat bicuspid aortic valve disease and isolated aortic regurgitation, the choice of THV type was reported to be important. Conclusions This survey-based study identifies key patient characteristics that impact THV selection. As such, we present a guide, based on current practice, of which THV types are best suited to these different patient-specific characteristics. A patient-tailored THV choice is likely to optimize TAVR outcomes.